2010
DOI: 10.1016/j.ecolecon.2010.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Integrated regulation of nonpoint pollution: Combining managerial controls and economic instruments under multiple environmental targets

Abstract: Further information on publisher's website:http://www.dur.ac.uk/business/faculty/working-papers/ Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…There is an increasing progress of researches on air or water pollution, deforestation, diversity and indicators of environmental amenities up until for some recent findings around the world (e. g. Kaika and Zervas, 2013;Katz, 2015;Wang et al, 2015Wang et al, , 2016a, also in China (e. g. Xu and Lin, 2015;Yao et al, 2016;Hao and Liu, 2016;Wang et al, 2016b). However, researches on the relationship between agriculture-related pollution and economic growth are relatively scanty (Shortle and Abler, 2001;Aftab et al, 2010), few of which were related to Environmental Kuznets Curve. To our knowledge, few other prior studies have tested the EKC in the case of these environmental issues arising from livestock and poultry breeding.…”
Section: Environmental Kuznets Curvementioning
confidence: 99%
“…There is an increasing progress of researches on air or water pollution, deforestation, diversity and indicators of environmental amenities up until for some recent findings around the world (e. g. Kaika and Zervas, 2013;Katz, 2015;Wang et al, 2015Wang et al, , 2016a, also in China (e. g. Xu and Lin, 2015;Yao et al, 2016;Hao and Liu, 2016;Wang et al, 2016b). However, researches on the relationship between agriculture-related pollution and economic growth are relatively scanty (Shortle and Abler, 2001;Aftab et al, 2010), few of which were related to Environmental Kuznets Curve. To our knowledge, few other prior studies have tested the EKC in the case of these environmental issues arising from livestock and poultry breeding.…”
Section: Environmental Kuznets Curvementioning
confidence: 99%
“…2 Farm groups are assumed to represent the agricultural sector at the regional level given and the Farm Accountancy Data Network (FADN) is the basis for calibration. In comparison to many bioeconomic models, the fact that we use a FADN sample of farms clustered into farm groups makes it possible to avoid problems of data confidentiality and account for farm heterogeneity (e.g., Aftab et al (2010Aftab et al ( , 2007 Jayet, 2000). The AROPAj calibration process keeps the production set large, so AROPAj findings allow land allocation among crops, as is seen, for instance, in cases of change in CAP and in price or tax (Jayet and Petsakos, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…More recently, significant advances have been made by applying this kind of model to problems arising in cases of non-point source pollution. However, most of these studies focus on salinity and river pollution rather than on aquifer pollution (Connor, 2008;Aftab et al, 2010Aftab et al, , 2007. In order to better understand the impact of policies dealing with water pollution, hydro-economic modeling integrates three components: hydrological, economic and agronomic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EIs cannot be the panacea to the DPA (due to the diffuse nature of the pollution). Aftab et al (2010) also suggested a mixed approach of economic incentives and management standards. Therefore, it is recommended that in designing a policy to solve the DPA, all the three major PIs need to be combined.…”
Section: Recommendations and Conclusionmentioning
confidence: 99%